Numbers Don't Lie: COVID-19 Legal Trends in ASEAN - Siradj Okta (Research Collaboration Community (RCC), 2021)
This study compares the COVID-19 legal trends among 10 ASEAN countries during March 2020-September 2021. The study is an explanatory project with quantitative approach in comparing the number of legislation in South East Asia. The study aims to obtain a credible quantitative report from the region. The report would be beneficial to future qualitative reasoning when in-depth individual country's pandemic profile is taken into account. The comparison examines the Covid Law Lab database, a joint collaboration between the World Health Organization (WHO), United Nations Development Programme (UNDP), the Joint United Nations Programme on HIV/AIDS (UNAIDS), the O'Neill Institute for National and Global Health Law and Georgetown University. Globally, among 4,880 Titles adopted in 192 countries, 1493 (31%) Titles are under the topic of 'movement and distancing restriction', followed by 470 (9%) Titles on 'state of emergency'. In ASEAN, 'movement and distancing restriction' remains the most legislated topic. The Philippines is recorded as the most legislating country in the region (150 Titles), followed by Myanmar (139 Titles) and Indonesia (138 Titles), while the least legislating country is Brunei Darussalam (1 Title). This study finds that COVID-19 legal trends in ASEAN is divergent to some extent from the global picture. Nonetheless, 'movement and distancing restrictions' legal topic is prevalent in the region and has led the 10 countries to its current pandemic situation.